Talking About Sex: Sexual Communication in the Context of Sexual Revictimization. - Beckham, Erin E.; Thompson, Mia S.; Duckworth, Jennifer C.; Jaffe, Anna E. (Journal of Child Sexual Abuse, 2026)
The relationship between sexual victimization and communication is crucial to examine, given research suggesting that effective and frequent communication about sexual activities helps facilitate safer sex behaviors, sexual functioning, and pleasure. Building on prior studies in this area, which tend to focus on assertiveness, the current study examines childhood sexual abuse (CSA), adolescent/adulthood sexual assault (ASA), and communication frequency across three domains: safer sex behaviors, sexual interests, and consent/boundaries. The sample consisted of 422 sexually-active undergraduates recruited from four U.S. universities (Mage = 19.77; 76.5% women). Moderation analyses revealed that more severe ASA was associated with more frequent communication about safer sex and consent, but only for those with a history of CSA. The elevated frequency of communication following more severe and repeated sexual victimization may highlight survivors' resilience in having ongoing conversations about safety in sexual situations.